Dr. The Effects of Unethical Marketing Practices on Nigerian Economy and the Quest for National Development: The Effects of Unethical Marketing Practices on Nigerian Economy and the Quest for National Development - Ayuba, Bello (Archives of Business Research, 2019)
ABSTRACT The main objective of the study is to examine the effects of unethical marketing practices on the Nigerian economy. As part of the methodology both primary and secondary sources of data were used. The data were analysed using Descriptive Statistics, Chi – square and Regression Analysis to test the formulated hypotheses which reveals that, “unethical marketing practices affects the country’s economy in the areas of economic growth such as decline in GDP, Increased inflationary activity, decline in patronage leading to closure of factories and plants and subsequently, unemployment, as well as bribery and corruption, poor infrastructure and the lack of innovative entrepreneurship skills”. The findings also, reveal that the socially irresponsible actions of some Nigerian business managers cause environmental degradation of some basic needs in the course of marketing activities through air pollution, land pollution and water pollution resulting to huge waste of solid, liquid and gaseous substance which threaten societal well-being. Among the major recommendations are the need for Federal government to ensure that business regulatory bodies are alive to their responsibilities by ensuring that adequate laws with stiffer penalties on violations of marketing ethics are strengthened to help in combating all the unethical marketing practices bedevilling the Nigerian society. The study concludes that marketers should note that they are responsible for most of the activities necessary to create more customers; they should know that customer’s satisfaction should be the ultimate goal of any marketing activity and this must be achieved through enhancing societal well-being by being ethical and socially responsible in their marketing activities by shunning all those practices that are deceptive, exploitative and dangerous to human life.